EVALUATION OF ANTIBACTERIAL PROPERTIES OF LEAF AND STEM EXTRACTS OF ANDROGRAPHIS ELONGATA T. AND. – AN ENDEMIC MEDICINAL PLANT OF INDIA - ALAGESABOOPATHI C (International Journal of Pharma and Bio Sciences, 2013)
The point of the present study was focused on investigating the antibacterial property of the acetone and aqueous extract of the leaves and stem of Andrographis elongata T. And. (Acanthaceae) using agar well diffusion manner against human pathogenic bacterial species, namely Bacillus cereus, Escherichia coli, Klebsiella pneumoniae and Staphylococcus aureus. In the present investigation all the extracts were found to be efficient against four human bacterial species, B. cereus, E. coli, K. pneumoniae and S. aureus susceptible to all the plant extracts. Among various extracts studied, the aqueous stem extract showed highest antibacterial potential against S. aureus (16.41 mm) followed by acetone extract (14.40 mm). The maximum control extent noted for aqueous extract of A.elongata leaves against B.cereus was 12.06 mm followed by acetone extract (10.37mm). The study suggests that the extract of part of the plant restrain modern extensive wide range of antibacterial screening. The antibacterial potentialities of aqueous extracts was prove to be maximum than that of acetone extracts. However the stem extract showed more inhibitory determine than the leaf extracts. This research suggests that original products acquired from A. elongata may contribute to the expansion of recent antimicrobial agents. It is the first report on the antibacterial potential of A. elongata.